Determinants of Paracentrotus lividus sea urchin recruitment under oligotrophic conditions: Implications for conservation management. (June 2016) - Oliva, Silvia; Farina, Simone; Pinna, Stefania; Guala, Ivan; Agnetta, Davide; Ariotti, Pierre Antoine; Mura, Francesco; Ceccherelli, Giulia
Abstract: Sea urchins may deeply shape the structure of macrophyte-dominated communities and require the implementation of sustainable management strategies. In the Mediterranean, the identification of the major recruitment determinants of the keystone sea urchin species Paracentrotus lividus is required, so that source areas of the populations can be identified and exploitation or programmed harvesting can be spatially managed. In this study a collection of eight possible determinants, these encompassing both the biotic (larvae, adult sea urchins, fish, encrusting coralline algae, habitat type and spatial arrangement of habitats) and abiotic (substrate complexity and nutritional status) realms was considered at different spatial scales (site, area, transect and quadrat). Data from a survey including sites subject to different levels of human influence (i.e. from urbanized to protected areas), but all corresponding to an oligotrophic and low-populated region were fitted by means of a generalized linear mixed model. Despite the extensive sampling effort of benthic quadrats, an overall paucity of recruits was found, recruits being aggregated in a very small number of quadrats and in few areas. The analysis of data detected substrate complexity, and adult sea urchin and predatory fish abundances as the momentous determinants of Paracentrotus lividus recruitment. Possible mechanisms of influence are discussed beyond the implications of conservation management. Highlights: Identification of the determinants of Paracentrotus lividus sea urchin recruitment under oligotrophic conditions through a modelling approach. Substrate complexity, abundances of adult sea urchins and of predatory fish identified as the significant determinants of P. lividus recruitment. Source areas of the populations at oligotrophic conditions could be recognized, so that exploitation can be spatially managed.